Peran dan Hambatan Lembaga Pemasyarakatan dalam Mendukung Pemulihan Mental Warga Binaan Pemasyarakatan Studi di Kantor Wilayah Kementrian Hukum dan Hak Asasi Manusia Sumatera Utara - Harry Julius Pratama Manalu; Janpatar Simamora (Universitas 17 Agustus 1945 Semarang, 2025)
Corrections is one of the subsystems in criminal justice in Indonesia which carries out legal implementation in the field of treatment of prisoners, inmates and children. Corrections function in providing services, guidance, social guidance, care, security and supervision for inmates, without exception. This function is carried out based on the regulations that have been regulated in the statutory provisions. When inmates are placed in correctional institutions, they tend to experience changes in mental health caused by stress and depression as well as feelings of loneliness experienced by inmates. Therefore, correctional institutions have a role in restoring the mental health experienced by inmates. In carrying out its role, correctional institutions also experience obstacles which of course can have an impact on the implementation of the role of correctional institutions. This research uses deep research methods with descriptive qualitative methods. The results of the research that has been conducted show that correctional institutions have a role in restoring the mental health experienced by inmates. This can be seen from the programs carried out by correctional institutions to support the recovery of the mental health of inmates, although there are several obstacles, correctional institutions are still trying to carry out their role.